THE RELATIONSHIP OF KNOWLEDGE ABOUT EXTERNAL GENITAL HYGIENE AND THE INCIDENCE OF VAGINAL DISCHARGE IN ADOLESCENT GIRL: SYSTEMATIC LITERATURE REVIEW - Hasbiya Ririe Soemantri; Emi Lindayani; Diding Kelana Setiadi (Buletin Veteriner Udayana, 2024)
One of the reproductive health problems that teenagers, especially women, often complain about is vaginal discharge. Poor and inappropriate care for the external genitalia can cause continuous vaginal discharge, if not treated it will impact the function of the female reproductive organs. Women's behavior in improving external genital hygiene is a necessary action to prevent infection of the genital organs. The aim of this paper is to examine the results of research findings regarding the relationship between adolescent knowledge about external genital hygiene and the incidence of vaginal discharge based on literature results. The method used was a systematic literature review with journal papers published in 2018-2024 on the Google Scholar and Science Direct databases so that 9 articles were obtained that were relevant to this research. The results of this systematic literature review show that a lack of knowledge among young women about how to properly care for their external genitalia can trigger vaginal discharge. The conclusion of this study is that there is a relationship between knowledge about external genital hygiene and the incidence of vaginal discharge. Suggestions for young women should increase their knowledge about vaginal discharge so that with good knowledge their genital hygiene behavior will be good. This effort can be achieved by reading a lot, watching television or seeking information from health workers.